The falcons of fire and ice - Karen Maitland (: Michael Joseph, 2012)
1564, Lisbon. The Inquisition displays its power and ruthlessly spreads fear. Heretics are tortured and burned. Any who oppose the Church's will realize that silence is preferable to a slow and agonizing death. Isabela, daughter of the Falconer at the Royal Court, is about to be caught in the Church's terrifying schemes.